An update on PUG-REST: RESTful interface for programmatic access to PubChem. Issue Volume 46:Issue W1(2018) (30th April 2018) - Kim, Sunghwan; Thiessen, Paul A; Cheng, Tiejun; Yu, Bo; Bolton, Evan E
Abstract: PubChem (https://pubchem.ncbi.nlm.nih.gov ) is one of the largest open chemical information resources available. It currently receives millions of unique users per month on average, serving as a key resource for many research fields such as cheminformatics, chemical biology, medicinal chemistry, and drug discovery. PubChem provides multiple programmatic access routes to its data and services. One of them is PUG-REST, a Representational State Transfer (REST)-like web service interface to PubChem. On average, PUG-REST receives more than a million requests per day from tens of thousands of unique users. The present paper provides an update on PUG-REST since our previous paper published in 2015. This includes access to new kinds of data (e.g. concise bioactivity data, table of contents headings, etc.), full implementation of synchronous fast structure search, support for assay data retrieval using accession identifiers in response to the deprecation of NCBI's GI numbers, data exchange between PUG-REST and NCBI's E-Utilities through the List Gateway, implementation of dynamic traffic control through throttling, and enhanced usage policies. In addition, example Perl scripts are provided, which the user can easily modify, run, or translate into another scripting language.